In Vitro Assessment of Tobacco Smoke Toxicity at the BBB: Do Antioxidant Supplements Have a Protective Role? - Hossain, Mohammed (BioMed Central, 2011)
BACKGROUND: Tobacco smoke (TS) contains highly reactive oxygen species (such as hydrogen peroxide, peroxynitrite, etc), which cause oxidative damage in vascular tissue and may exacerbate inflammatory events leading to the blood-brain barrier damage (BBBD) which accompanies the development of a variety of neurological disorders. Smokers often have elevated leukocyte counts (primarily neutrophils and monocytes), and significant decreases in plasma alpha-tocopherol (vitamin E) and ascorbic acid (vitamin C) levels due to increased anti-oxidative mobilization in response to oxidative stress evoked by TS. For this purpose, using static culture systems and a well-established dynamic in vitro BBB model (DIV-BBB) we tested the hypothesis that antioxidant vitamin supplementation (E and/or C) can protect the BBB during exposure to whole soluble TS. RESULTS: TS exacerbates inflammatory events and leads to endothelial overexpression of vascular adhesion molecules (VCAM-1, P-selectin and E-selectin), release of pro-inflammatory cytokines (TNF-α and IL-6) and nitric oxide (NO), release and activation of matrix metalloproteinases (MMP-2 and MMP-9), monocytic maturation into macrophages, and adhesion to the vascular endothelium. Furthermore, TS altered the normal glucose metabolic behaviour of in vitro BBB capillaries and caused a period of transient anaerobic respiration to meet the cellular bioenergetic demand. Pre-treatment with antioxidant vitamins (C and/or E) effectively reduced the pro-inflammatory activity associated with TS, protecting the viability and functions of the BBB. CONCLUSION: Our results have shown that loss of endothelial viability as well as BBB function and integrity caused by TS exposure can be prevented or at least reduced by normal physiologic concentrations of antioxidant vitamins in vitro.